Decoding Digital Slang: A Sociolinguistic Analysis of Language Variation in @cursedkidd's Posts on X - Saskia Rimadita Syahban; Indah Sintya Sari; Erike Febri Naisilah; Damar Arif Adjie Saputra; Bimo Nur Muhammad Rozaq (KIRANA : Social Science Journal, 2026)
The rapid growth of social media has contributed to the emergence of diverse language varieties that reflect the dynamics of digital communication, particularly among young people. One prominent phenomenon is the use of slang language in posts shared by the X account @cursedkidd, which is recognized for its creative, concise, and humorous linguistic style. This study aims to analyze the forms of slang language employed in the account's posts and to explore their social functions and communicative characteristics within digital interactions. A descriptive qualitative approach employing content analysis was adopted. The data consisted of selected posts from @cursedkidd containing slang expressions, which were analyzed through data reduction, categorization, data display, and conclusion drawing. The findings reveal that the dominant linguistic features include word shortening, letter omission, spelling modification, and creative slang formations. These language varieties function to construct group identity, strengthen social solidarity, enhance communication efficiency, and create humorous expressions that resonate with young audiences. However, excessive reliance on slang may reduce users' ability to employ standard Indonesian appropriately in formal contexts. This study concludes that slang language on social media represents not only linguistic innovation but also a reflection of the evolving communication patterns of contemporary youth in digital environments.